Análisis De La Ciencia, El Método Científico, Las Relaciones Sociales Y La Educación Desde La Complejidad - Fuertes Andrade Delia María; León Fuentes Narciza de Jesús; Aldawsari Peñaherrera Nadá Rocío; Andrade Rivera Guadalupe Esperanza (International Journal of Education, Teaching, and Social Sciences, 2022)
Science and the appropriate methods to discover-build them, has a long history, in our history. Complexity has opened new paths for us, dispelling humanity's fears for discovering knowledge, breaking paradigms, applying the new method, learning to work with generative principles and building a new society. In this document you understand and explain the evolution of our society and education, the influence of the scientific method, and that of the complexity method, to cement our society